2020
DOI: 10.1007/978-1-0716-0434-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Native Chemical Ligation via N-Acylurea Thioester Surrogates Obtained by Fmoc Solid-Phase Peptide Synthesis

Abstract: Native chemical ligation (NCL) enables the direct chemical synthesis and semisynthesis of proteins of different sizes and compositions, streamlining the access to proteins containing posttranslational modifications (PTMs). NCL assembles peptide fragments through the chemoselective reaction of a C-terminal α-thioester peptide, prepared either by chemical synthesis or via intein-splicing technology, and a recombinant or synthetic peptide containing an N-terminal Cys. Whereas the generation of C-terminal α-thioes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Intramolecular native chemical ligation (NCL) is the most widely used technique for cyclizing linear cyclotide precursors containing a cysteine and an α-thioester group in the N-terminal and C-terminal ends respectively. [28] The process can be performed at physiological pH and can theoretically be accomplished between six cysteine amino acids found in the peptide structure. Yet, research on natural cyclotides (kalata B1 and MCoTIÀ I/II) suggested that the cyclization yield is highly improved when the cysteines are located in loops 3 and 6.…”
Section: Native Chemical Ligation (Ncl)mentioning
confidence: 99%
“…Intramolecular native chemical ligation (NCL) is the most widely used technique for cyclizing linear cyclotide precursors containing a cysteine and an α-thioester group in the N-terminal and C-terminal ends respectively. [28] The process can be performed at physiological pH and can theoretically be accomplished between six cysteine amino acids found in the peptide structure. Yet, research on natural cyclotides (kalata B1 and MCoTIÀ I/II) suggested that the cyclization yield is highly improved when the cysteines are located in loops 3 and 6.…”
Section: Native Chemical Ligation (Ncl)mentioning
confidence: 99%
“…The linear sequences were cyclized using an intramolecular version of NCL 157 via N- acylurea (Nbz) thioester surrogates. 120 , 158 , 159 Upon cyclization, the cyclotides were folded under oxidative conditions. 120 122 …”
Section: Experimental Sectionmentioning
confidence: 99%
“…Peptides were manually assembled on a H 2 N-Rink-ChemMatrix resin (1.0 mmol scale, 7-fold excess of amino acid, HBTU:DIPEA 7:10.5-fold activation, 30 min coupling time). The linear sequences were cyclized using an intramolecular version of NCL via N- acylurea (Nbz) thioester surrogates. ,, Upon cyclization, the cyclotides were folded under oxidative conditions. …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The corresponding C‐terminal peptides SELENOF(141‐165)(A141U) was synthesized by Fmoc‐SPPS, purified and characterized by HPLC and ESI‐MS (Scheme S1, Figure S1). Both SELENOF(96‐140)(Sec96Sez)‐COSR and SELENOF(89‐95)‐COSR (Schemes S2 and S3), bearing a C‐terminal thioester [27] were prepared similarly by standard stepwise Fmoc‐SPPS (further details for the syntheses can be found in Supporting Information 4.3 and Figures S2–S4) [27a,28] . The ligation between SELENOF(96‐140)(Sec96Sez)‐COSR and SELENOF(141‐165)(A141U) was performed at 37 °C for 18 h in the presence of TCEP and sodium ascorbate [29] to yield SELENOF(96‐165)(Sec96Sez/A141U) (Figure S5).…”
Section: Figurementioning
confidence: 99%
“…Both SELENOF(96‐140)(Sec96Sez)‐COSR and SELENOF(89‐95)‐COSR (Schemes S2 and S3), bearing a C‐terminal thioester [27] were prepared similarly by standard stepwise Fmoc‐SPPS (further details for the syntheses can be found in Supporting Information 4.3 and Figures S2–S4). [ 27a , 28 ] The ligation between SELENOF(96‐140)(Sec96Sez)‐COSR and SELENOF(141‐165)(A141U) was performed at 37 °C for 18 h in the presence of TCEP and sodium ascorbate [29] to yield SELENOF(96‐165)(Sec96Sez/A141U) (Figure S5). To convert Sec141 to Ala, the purified ligated product was subjected to deselenization reaction with TCEP at pH∼5, and under anaerobic conditions.…”
mentioning
confidence: 99%